Soil Biology Contribution on Agricultural Land Suitability Evaluation of Wet Tropical Megabiodiversity Regions - GITOSUWONDO, SUBOWO; SANTOSA, EDI; ANAS, ISWANDI (Jurnal Sumberdaya Lahan, 2010)
Indonesia is in the region "wet tropical megabiodiversity" it would need to complete the systemÂ  for agricultural land suitability evaluation in accordance with real conditions, thus increasing the value-added resources optimally and sustainable and accountable production investment. Soil organisms as a component of production support can act as an agent of energy and nutrient cycling in the soil, improving soil physical properties, and controlling pests and disease. For that soil, biological parameters that need to be considered in evaluating the suitability of land that already exist include: N-fixing or P-solubilizing bacteria groups that live symbiosis and free-living, the fungi solubilizing P and soil organic matter decomposition groups, BGA fixing and free-living N symbiotic groups, fauna groups are able to conserve soil organic matter and improve soil physical properties. Important steps that need to be done in the evaluation of land cover inventory of soil biological populations and its role on the growth of crops, and evaluate the suitability of the soil biological parameters of the functional value of commodity options.